Evaluación de carbono orgánico edáfico bajo distintos usos de suelo en la microcuenca San Simón, cantón Loja - Diaz Sarango, Wagner Servio (2024)
The San Simón micro-watershed area, located in El Carmen - Loja, is vital for carbon storage. However, the conversion of forests into agricultural and livestock lands has compromised this important ecosystem service, altering the environmental functionality of the area. The main objective of this research was to evaluate COS (soil organic carbon) storage in three land uses (forest, crop, and pasture) within the San Simón micro-watershed. In each land use, one hectare was delineated, and samples were taken at a depth of 15cm: 6 undisturbed samples to measure bulk density, and 3 composite samples to analyze organic matter and organic carbon. For statistical processing, SPSS and InfoStat software were used. According to the study's findings, the San Simón micro-watershed area contains a total of 315.24 tC ha−1, distributed differently depending on land use: the forest holds 117.94 tC ha−1, crops 107.08 tC ha−1, and pastures 90.22 tC ha−1. Regarding soil bulk density, it was observed that areas dedicated to crops and forests showed lower values, while the pasture area recorded a maximum value. However, the study revealed that the relationship between carbon percentage and organic matter reached its minimum in pasture areas. The comparative analysis showed statistically significant differences in COS content among the studied land uses, which can be attributed to environmental factors (temperature, humidity, altitude, precipitation), soil characteristics, and practices such as overgrazing. The forest showed a higher COS content compared to other land uses. Likewise, the physical (bulk density) and chemical (organic carbon, organic matter) properties of the soil influenced COS content in the micro-watershed area.